Tartas 1, Russische Föderation. Neue Grabfunde der Bronzezeit und die erste neolithische Sequenz aus Westsibirien – Fortsetzung der Ausgrabungen in Tartas 1 und Umgebung. Die Arbeiten der Jahre 2015 bis 2018 - Reinhold, Sabine (e-Forschungsberichte des DAI, 2019)
Since 2004, the Eurasia-Department has been cooperating with the Institute of Archaeology and Ethnology RAS in Novosibirsk on excavating sites of the Bronze Age in Western Siberia. The research focuses on the site of Tartas 1, where until today more than 730 burials from the Bronze Age (4rd to 1st millennium BC) have been examined. Surprisingly, Neolithic settlement remains, until today two houses and at least 12 deep pits, were uncovered in 2015. They offer the first radiocarbon dated Neolithic sequence in Siberia in the 7th millennium BC. Since 2017, a new site nearby with similar complexes has been excavated.